Neutral and charged boron-doped fullerenes for CO2 adsorption - de Silva, Suchitra W.; Du, Aijun; Senadeera, Wijitha; Gu, Yuantong (Beilstein Journal of Nanotechnology, 2014)
Recently, the capture and storage of CO2 have attracted research interest as a strategy to reduce the global emissions of greenhouse gases. It is crucial to find suitable materials to achieve an efficient CO2 capture. Here we report our study of CO2 adsorption on boron-doped C60 fullerene in the neutral state and in the 1e−-charged state. We use first principle density functional calculations to simulate the CO2 adsorption. The results show that CO2 can form weak interactions with the BC59 cage in its neutral state and the interactions can be enhanced significantly by introducing an extra electron to the system.
Keywords: adsorption; boron doping; CO2 capture; density functional theory (DFT); heterofullerene

World Energy Outlook 2011 - International Energy Agency (IEA Publications, 2011)

(untitled) - Kheshgi, H.; de Coninck, H.; Kessels, J. (Mitigation and Adaptation Strategies for Global Change, 2012)

(untitled) - Lee, K. B.; Sircar, S. (AIChE J., 2008)

(untitled) - Jiao, Y.; Du, A.; Zhu, Z.; Rudolph, V.; Smith, S. C. (J. Mater. Chem., 2010)

(untitled) - Jiao, Y.; Du, A.; Zhu, Z.; Rudolph, V.; Smith, S. C. (J. Phys. Chem. C, 2010)

(untitled) - Sun, Q.; Wang, M.; Li, Z.; Du, A.; Searles, D. J. (J. Phys. Chem. C, 2014)

(untitled) - Lee, H.; Li, J.; Zhou, G.; Duan, W.; Kim, G.; Ihm, J. (Phys. Rev. B, 2008)

(untitled) - Sun, Q.; Li, Z.; Searles, D. J.; Chen, Y.; Lu, G. (M.); Du, A. (J. Am. Chem. Soc., 2013)

(untitled) - Chen, Z.; King, R. B. (Chem. Rev., 2005)

(untitled) - Tenne, R. (Adv. Mater., 1995)

(untitled) - Gao, B.; Zhao, J.-x.; Cai, Q.-h.; Wang, X.-g.; Wang, X.-z. (J. Phys. Chem. A, 2011)

(untitled) - Gao, F.; Zhao, G.-L.; Yang, S.; Spivey, J. J. (J. Am. Chem. Soc., 2013)

(untitled) - Guo, T.; Jin, C.; Smalley, R. E. (J. Phys. Chem., 1991)

(untitled) - Zou, Y. J.; Zhang, X. W.; Li, Y. L.; Wang, B.; Yan, H.; Cui, J. Z.; Liu, L. M.; Da, D. A. (J. Mater. Sci., 2002)

(untitled) - Dunk, P. W.; Rodríguez-Fortea, A.; Kaiser, N. K.; Shinohara, H.; Poblet, J. M.; Kroto, H. W. (Angew. Chem., 2013)

(untitled) - Wang, S.-H.; Chen, F.; Fann, Y.-C.; Kashani, M.; Malaty, M.; Jansen, S. A. (J. Phys. Chem., 1995)

(untitled) - Kurita, N.; Kobayashi, K.; Kumahora, H.; Tago, K.; Ozawa, K. (Chem. Phys. Lett., 1992)

(untitled) - Sun, Q.; Wang, M.; Li, Z.; Ma, Y.; Du, A. (Chem. Phys. Lett., 2013)

(untitled) - Jiao, Y.; Zheng, Y.; Smith, S. C.; Du, A.; Zhu, Z. (ChemSusChem, 2014)

(untitled) - Becke, A. D. (J. Chem. Phys., 1993)

(untitled) - Lee, C.; Yang, W.; Parr, R. G. (Phys. Rev. B, 1988)

(untitled) - Stephens, P. J.; Devlin, F. J.; Chabalowski, C. F.; Frisch, M. J. (J. Phys. Chem., 1994)

(untitled) - Grimme, S. (J. Comput. Chem., 2006)

(untitled) - Grimme, S.; Ehrlich, S.; Goerigk, L. (J. Comput. Chem., 2011)

(untitled) - Mulliken, R. S. (J. Chem. Phys., 1955)

(untitled) - Simon, S.; Duran, M.; Dannenberg, J. J. (J. Chem. Phys., 1996)

(untitled) - Boys, S. F.; Bernardi, F. (Mol. Phys., 1970)

(untitled) - Peng, C.; Schlegel, H. B. (Isr. J. Chem., 1993)

Finding minima, transition states, and following reaction pathways on ab initio potential energy surfaces - Hratchian, H. P.; Schlegel, H. B. (Elsevier, 2005)

(untitled) - Peng, C.; Ayala, P. Y.; Schlegel, H. B.; Frisch, M. J. (J. Comput. Chem., 1996)

(untitled) - Gonzalez, C.; Schlegel, H. B. (J. Chem. Phys., 1989)

Gaussian 09, Revision B.01 (Gaussian, Inc., 2009)

GaussView, Version 5 (Semichem Inc., 2009)

(untitled) - Kim, K.-C.; Hauke, F.; Hirsch, A.; Boyd, P. D. W.; Carter, E.; Armstrong, R. S.; Lay, P. A.; Reed, C. A. (J. Am. Chem. Soc., 2003)

(untitled) - Xie, R.-H.; Bryant, G. W.; Zhao, J.; Smith, V. H., Jr.; Di Carlo, A.; Pecchia, A. (Phys. Rev. Lett., 2003)

(untitled) - Chu, S.; Majumdar, A. (Nature, 2012)

Exploring chemistry with electronic structure methods: A Guide to Using Gaussian - Foresman, J. B.; Frisch, Æ. (Gaussian, Inc., 1996)